GENDING-GENDING RARE DI DESA BALI AGA DI KABUPATENKARANGASEM ANALISIS MAKNA - Darmawati, Ni Luh Putu (Humanis, 2014)
Research on Rare Gending-Gending Bali Aga village in Karangasem regency has the goal to describe the meaning of Yanga are in the rare gising. The theory used is semiotik.Teori semiotic theory applied that theory to explore the meaning of Saussure is in gending rare.The study was conducted by using method sand techniques that are divided into three stages:(1) Stag eprovision of data using observational methods to observe gending rare in the field, consider the method proposed by Sudaryanto accompanied by refer-free techniques involved conversation(SBLC), method of conversation with fishing techniques, methods of interview swith recording techniques, technical translation, and technical notes.(2) phase of the data analysisis done by reading the data followed a descriptive analytic method proposed by Ratna, classification, accompanied by quantitative and qualitative methods by Sugiyono. (3) Stage presentation of the data using informal methods of Sudaryanto data to formulate words.The results obtained on gending rare covering the meaning contained meaning struggle, the meaning of culture, magical, loving environment, and harmony.
Keywords: Gending Rare, Bali Aga, meaning.